The Role of the Food Crops, Horticulture and Plantation Office of Sorong Regency in the Farmers Group in Salawati District - Ivonne M. Leiwakabessy (Universitas Muhammadiyah Sorong, 2021)
Life that comes from food must inevitably be fulfilled, the involvement of the local economy will inevitably bring serious challenges. So it is reasonable to say that globalization will bring benefits if the response of national and local governments can properly mobilize local resources. The resources that are owned in relation to farming groups cannot be separated from the role of local governments in efforts to improve a decent life for farmers and the farming groups themselves. The research was carried out at the Food Crops, Horticulture and Plantation Service of Sorong Regency against the Farmers Group in Salawati District from June to September 2020. This research used descriptive methods by survey and cross sectional methods which used samples from the Department of Agriculture and farming groups in the District. Salawati. The analysis used is a Likert scale and a frequency table. Based on the results of the analysis, the role of the Agricultural Instructor as Motivator, Facilitator, Communicator and Innovator is in the very good category, while the participation of farmers in the role of the Dinas is in the Good category. Thus the suggestion that is conveyed is the active role of every institution involved both as extension workers and farmers who are pro-active in carrying out their duties and responsibilities. This score or number will be at 100 percent if all parties can carry out the function properly.